2003
DOI: 10.1002/pmic.200300590
|View full text |Cite
|
Sign up to set email alerts
|

Pattern analysis of serum proteome distinguishes renal cell carcinoma from other urologic diseases and healthy persons

Abstract: Despite having a relatively low incidence, renal cell carcinoma (RCC) is one of the most lethal urologic cancers. For successful treatment including surgery, early detection is essential. Currently there is no screening method such as biomarker assays for early diagnosis of RCC. Surface-enhanced laser desorption/ionization-time of flight mass spectrometry (SELDI-TOF) is a recent technical advance that can be used to identify biomarkers for cancers. In this study, we investigated whether SELDI protein profiling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 10 publications
2
52
0
2
Order By: Relevance
“…Indeed, SELDI-TOF MS has also been performed to identify biomarker proteins for early detection of RCC. Two studies describe protein profiling of serum with SELDI-TOF MS. 8,9 Tolson et al 8 reported a peak cluster at a mass-to-charge ratio (m/z) of approximately 11 000 from serum amyloid a-1 and variants, which was 100% specific for RCC compared to HC, although not very sensitive (detection in eight of 25 patients). Five m/z values of 3900, 4107, 4153, 5352 and 5987 were reported by Won et al 9 in a classification tree separating RCC from healthy and non-RCC urologic disease, with sensitivities and specificities ranging from 80 to 100%.…”
mentioning
confidence: 99%
“…Indeed, SELDI-TOF MS has also been performed to identify biomarker proteins for early detection of RCC. Two studies describe protein profiling of serum with SELDI-TOF MS. 8,9 Tolson et al 8 reported a peak cluster at a mass-to-charge ratio (m/z) of approximately 11 000 from serum amyloid a-1 and variants, which was 100% specific for RCC compared to HC, although not very sensitive (detection in eight of 25 patients). Five m/z values of 3900, 4107, 4153, 5352 and 5987 were reported by Won et al 9 in a classification tree separating RCC from healthy and non-RCC urologic disease, with sensitivities and specificities ranging from 80 to 100%.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][15][16][17][18][19][20][21]25 The most interesting discovery of the study was the finding that a SELDI-derived peak (m/z 4,462) was as effective at discriminating cancer from benign serum as the tumor markers CEA or CA19.9, while combining these three serum markers marginally improved classification. Classification could be further improved with data generated from a panel of peaks, suggesting analysis of proteomic profiles, rather than individual proteins, may yield improved diagnostic ability.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][15][16][17][18][19][20][21]25 A potential source of error in the tissue group not present in the serum study may be sampling error. The high desmoplastic nature of CCs means the sampled tissue may miss the malignant portion of the tumor and may mainly consist of stroma rather than cholangiocytes proper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques can also be used to identify specific CSF biomarkers of CNS diseases that could be used for their detection, diagnosis, and monitoring [11][12][13][14]. 2-DE has been the gold standard for protein separation, and its combination with MS has led to the identification of numerous proteins within the normal CSF as well as potential protein markers for neurodegenerative diseases, demyelinating diseases, Creutzfeld Jacob Disease (CJD), primary CNS neoplasms, and other neurologic disorders [15,16].…”
Section: Introductionmentioning
confidence: 99%